Clinical and Epidemiological Characteristics of Pediatric Pertussis Cases in a specialized hospital in Mexico - Itzel Stella Pérez Campos; Ricardo Gil Guevara; Pedro Arturo Mejía Rosales; Ana Estela Gamiño Arroyo; Ana Carmen Guerrero Diaz; Fernando Ortega Ríosvelasco (Journal of the Pediatric Infectious Diseases Society, 2026)
Abstract Background Whooping cough is an acute respiratory infection caused by Bordetella pertussis, with a high transmissibility and risk of serious complications in children, particularly infants. These characteristics make the infection a global health challenge. Although vaccination programs are well-established, declining coverage and resulting incomplete schedules have led to a resurgence of cases in recent months, especially in children under five years of age. These patients often present with severe symptoms requiring hospitalization and, in many cases, even ventilatory support. Clinical and epidemiological characterization in tertiary institutions is essential to strengthen prevention, early diagnosis, and vaccination strategies. Methods We performed a descriptive, observational study of pertussis cases due to Bordetella pertussis from June 2024 to June 2025. The cases met the operational definition of pertussis syndrome and were confirmed using Film Array. Results A total of 24 confirmed cases were reported: six (25%) during 2024 and 18 (75%) during 2025. Eleven (45%) were female, 14 (58%) were younger than 1 year of age, eight (33%) were between 1 and 3 years of age, one case was five years old, and one was 12 years old. According to their state of residence, 16 (67%) were from the State of Mexico, 7 (29%) from Mexico City, and one case from Guerrero. The clinical symptoms they presented were: cough (96%), paroxismal cough (83%), cough in spasms (70%), cyanizing cough (63%), apnea or cyanosis (80%), laryngeal stridor (12%), emetizing cough (42%), fever (29%), this remained between 37.8 and 39 ° C, respiratory difficulty was reported (95%), desaturation (54%) and tachycardia (50%). They had an average evolution of 19 days before going to the hospital. Upon admission, 92% required ventilatory support, 70% with nasal cannula, 29% with a bag-reservoir mask, 12% required noninvasive mechanical ventilation, and 12% were intubated, 30% were admitted to intensive care, 80% of the cases presented leukocytosis. None of the cases had a complete vaccination schedule for their age, and 45% did not have a vaccination record. Ninety-two percent had already received treatment prior to admission, and 44% were previously healthy. Conclusion An increase in cases has been observed worldwide (1), associated with a decrease in vaccination coverage (1). The lack of vaccination, timely identification of cases, and adequate treatment results in patients presenting with severe conditions. Promoting vaccination, timely diagnosis, and treatment is essential to breaking the chains of transmission and protecting the population.